2007
DOI: 10.2174/138945007780618490
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Ampakine Modulators: From AMPA Receptors to Synapses and Behavior

Abstract: Ampakines are drugs structurally derived from aniracetam that potentiate currents mediated by AMPA type glutamate receptors. These drugs slow deactivation and attenuate desensitization of AMPA receptor currents, increase synaptic responses and enhance long-term potentiation. This review focuses mainly on recent physiological studies and on evidence for two distinct subfamilies. Type I compounds like CX546 are very effective in prolonging synaptic responses while type II compounds like CX516 mainly increase res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 0 publications
2
162
0
Order By: Relevance
“…If so, then amplifying theta burst responses could allow TBS1 to induce LTP machinery in the high threshold cases. We tested this using a positive allosteric modulator of AMPA-type glutamate receptors (18,19) to increase the composite depolarization produced by TBS1 (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…If so, then amplifying theta burst responses could allow TBS1 to induce LTP machinery in the high threshold cases. We tested this using a positive allosteric modulator of AMPA-type glutamate receptors (18,19) to increase the composite depolarization produced by TBS1 (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…decrease receptor desensitization or deactivation) [57,58]. AMPA receptor potentiating drugs increase the size of EPSPs, enhance LTP, enhance learning and memory, and increase BDNF [59,60].…”
Section: Potential Synaptogenic Targetsmentioning
confidence: 99%
“…There were reports indicating that endogenous BDNF level could be elevated by short-term administration of specific compounds, for example, the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid AMPA receptor modulator ampakine [58] . Ampakines are a group of small molecules that can delay deactivation and reduce desensitization of AMPA type glutamate receptors and thereby increase the size and duration of ligand-gated current flow, enhancing glutamate transmission [59,60] . In addition, previous studies showed that regular ampakine administration would increase the expression of BDNF.…”
Section: Future Directionsmentioning
confidence: 99%